ANALYSIS OF EMPLOYEE CAREER DEVELOPMENT AT LPP TVRI SOUTHEAST SULAWESI - Nurwati , Nurwati (Jurnal Multidisipliner Bharasumba, 2025)
This research was conducted with the aim of analyzing and identifying the career development of employees at LPP TVRI Southeast Sulawesi. The data used in this study were obtained through interviews and analyzed using descriptive analysis. There were four informants involved in this research. The results show that the career development of employees at LPP TVRI Southeast Sulawesi: (1) has good organizational policies for developing employees’ careers, providing equal opportunities for all employees; (2) good work performance is an important aspect considered by LPP TVRI Southeast Sulawesi as the basis for employee guidance and career development; (3) educational background is very important as one of the main references for LPP TVRI Southeast Sulawesi in improving employee careers; (4) employee training at TVRI Southeast Sulawesi is well-facilitated and routinely conducted, (5) work experience reflects the level of knowledge and skills mastered by employees in their work, which can be measured by length of service and the level of knowledge and skills possessed; (6) employees who demonstrate long-term loyalty and dedication to LPP TVRI Southeast Sulawesi are taken into consideration as a requirement for career development; (7) building cooperation among employees as well as between leaders and employees at LPP TVRI Southeast Sulawesi is essential to create an environment with shared understanding, aligned frequency, and a common vision and mission.